THE WHITE MAN'S BURDEN: ON THE EFFECT OF AFRICAN RESISTANCE TO EUROPEAN DOMINATION - Kodila-Tedika, Oasis; Asongu, Simplice A; Cinyabuguma, Matthias (Journal of economic development, 2024)
The empirical evidence is based on instrumental variable and treatment effect estimation techniques. According to Adu (1987a, 1987b), in 1880 only about 20% of Africa was occupied or controlled by the colonial powers or colonists. According to the narrative at the time, the partition of Africa was an eloquent testimony of capitalism and a display of the superiority of the 'white race' with overtones drawn from then popular theories such as social Darwinism and social Atavism. Here he describes the resistance movements which, while being directed against African aristocracy, were also a defence against French economic aggression. 4 In short, in this part of Africa, there were several uprisings or rebellions, inter alia: that of Mamadou Lamine in Senegal between 1885 and 1887 and those of Fode Kabba the wizard King of Kombo and Fode Kabba, the Muslim head of Niamina and district of Casamance in Gambia between 1898 and 1901; the rebellion caused in 1898 by taxes in Sierra Leone, led by Bai Bureh; that of Ashanti Gold Coast in 1900, under the direction of the Queen of Edweso Nana YaaAsantewaa; that of Ekumeku from 1898 to Africa was almost complete.